The Relationship Between Shoulder Range of Motion and Arm Stress in College Pitchers: A MOTUS Baseball Study. Issue 7 (31st July 2020) - Gulledge, Caleb; Jildeh, Toufic; Tramer, Joseph; Meta, Fabien; Taylor, Kevin; Smith, Grace; Makhni, Eric; Okoroha, Kelechi; Moutzouros, Vasilios; Khalil, Lafi
Objectives: Overuse injuries in overhead athletes are becoming more prevalent, with an unclear relationship between shoulder biomechanics and medial elbow symptoms and injury. The purpose of this study was to investigate the relationship of shoulder range of motion to torque across the medial elbow in college pitchers using a validated MOTUS sensor baseball sleeve. Methods: Pitchers were recruited from three local university baseball teams. Exclusion criteria included injury or restricted activity due to pain. They were evaluated in the preseason, within two weeks before their first game of the season. Pitchers completed workload questionnaires and patient reported outcome measurement information system (PROMIS) pain interference (PI), physical function (PF), and upper extremity (UE) surveys. Shoulder range of motion and upper extremity lengths were measured bilaterally. After adequate warm-up, pitchers were fitted with a MOTUS sensor baseball sleeve (Motus Global, Massapequa, NY) and instructed to throw 5 fastballs in a standardized manner off the mound at game-speed effort. The sensor placed at the medial elbow reported elbow torque, arm speed, arm slot, and shoulder rotation for each pitch, while a radar gun measured peak ball velocity. The primary outcome was to evaluate the relationship between shoulder range of motion and increased stress across the medial elbow. Additional outcomes evaluated pitcher characteristics, demographics, and outcome scores. Outcomes were assessed via a multivariable model, which controlled for possible covariates. Results: Twenty-eight pitchers were included in the preseason analysis with an average (SD) age of 20.1 (1.3) years and playing experience of 15.3 (1.8) years, 2.5 (1.2) of those years at collegiate level. The dominant shoulder demonstrated decreased internal rotation (54.5+/-10.6 vs 65.8+/-9.1) and increased external rotation (ER, 94.1+/-10.4 vs 88.4+/-9.2) relative to the non-dominant side (p < 0.001), while total rotational range of motion (TRROM) was significantly decreased in the dominant arm (148.6+/-12.4 vs 154.1+/-10.6, p < 0.001). The average glenohumeral internal rotation deficiency (GIRD) was 11.3 (9.87) and average external rotation gain (ERG) was 5.71 (8.8). External rotation was found to be a predictor of arm stress, with an increase in 0.35 Nm of elbow torque for every degree increase in ER (beta = 0.35+/-0.06, p = 0.003); there was moderate correlation between ER and arm stress (r = .45, P<.001). Pitchers demonstrated significantly greater arm stress with the following shoulder ROM measurements: GIRD < 20 as compared to greater than 20 degrees (46.6 +/- 0.5 versus 43.5 +/- 1.1, P=.011), ERG greater than 5 as compared to < 5 degrees (47.4 +/- 0.7 versus 45.1 +/- 0.6, P=.014), and loss of total rotational ROM less than 5 as compared to > 5 degrees (46.6 +/- 0.5 versus 43.6 +/- 1.1, P=.013). Multivariate analysis demonstrated significant predictors of PROMIS PF and UE scores were arm stress, ERG, and GIRD (p<0.05), while increased PROMIS PI scores were predicted by increased ERG and GIRD (p<0.05). Conclusion: We found medial elbow stress, arm speed, arm slot, and shoulder rotation as measured by the MOTUS baseball sensor sleeve were influenced by rotational adaptations of the pitching shoulder in collegiate throwing athletes prior to their season. Likewise, arm stress and shoulder rotational adaptations were reflected as predictors of PROMIS PF, UE, and PI scores.